Hubungan Perilaku Asertivitas dengan Bystander Response pada Situasi Bullying Siswa SD Negeri di Kecamatan Pariaman Tengah - Ramadhan, Muhammad Gilang; Aulia, Farah (TSAQOFAH, 2025)
This study aims to examine the relationship between assertiveness and the defender-type bystander response in bullying situations among elementary school students in Pariaman Tengah Subdistrict. A quantitative approach with a correlational design was used, focusing on how assertive behavior influences students’ tendency to act as defenders in bullying cases. Purposive sampling was employed to select research participants, involving 222 students from several public elementary schools in the region. Data were collected using an assertiveness questionnaire and the Short Bullying Bystander Scale (SBBS) from the Participant Role Questionnaire, and analyzed using the Pearson Product Moment correlation technique. The results show a low but significant positive relationship between assertiveness and defender-type bystander response (r = 0.378; p < 0.05). This finding indicates that the higher a student’s level of assertiveness, the greater their tendency to intervene and defend victims of bullying. The study concludes that fostering assertive behavior is a key intervention strategy in encouraging prosocial responses to bullying, and in empowering students to become active contributors to a safe and inclusive school environment.